Self-assembly of [60]fullerene-thiol derivatives on mercury surfaces - Song, Fayi (Langmuir : the ACS journal of surfaces and colloids, 2005)
Herein we report the first self-assembly of fullerene-thiol conjugates (1 and 2) on thin mercury films (TMF) deposited on a glassy carbon electrode (GCE). The fullerene-containing SAMs were investigated by cyclic voltammetry and water contact angle measurements. Two reversible, surface-confined redox couples were obtained for the fullerene-containing SAMs on TMF/GCE in CH(2)Cl(2) solution. The surface coverage of both fullerene derivatives 1 and 2 on TMF/GCE was measured to be in the range of (1.7-1.8) x 10(-10) mol cm(-2). Both SAMs of 1 and 2 partially blocked the electron transfer across the electrode in aqueous solution. The contact angle measurements performed on TMFs clearly showed an enhancement of the surface hydrophobicity upon formation of the fullerene-containing monolayer